Philosophical and Socio-political Views of Muhammed Hadi - Alakbarli, Faig (Scholarya Demo Journal of Ruby, 2020)
The article discusses the issues of nationality, religion and modernization, as well as philosophical problems in Turkish poet-thinker Muhammad Hadi’s worldview. According to the author, the most remarkable issues in Hadi’s socio-political worldview were the revival and enlightenment of the Azerbaijani people. The article also extensively investigates Hadi’s comparison of Oriental culture with Western culture. According to the author, Hadi was right to defend the idea that in the modern era, the people in the West were learning science and art strengthening their industry and armed forces, while people in the East still considered science as opposed to Islam calling it a deceptive act. However, Hadi’s attitude towards pan Pan Islamism, Turkism and modernization was objective. The article also sheds light on several philosophical issues in Hadi’s works. According to the author, the poet has made a number of philosophical generalizations as he seeks answers to questions arising in his consciousness about the origin of the world as well as human and whether there was any purpose in the birth of man. Consequently, Hadi was not directly concerned with the problem of existence and cognition but was indirectly interested in some philosophical issues. Hadi’s ontological views also show a tendency toward pantheism, including sufism. According to the author, while Hadi first saw the causes of profound change and transformation in society as a divine force, he later favored the evolutionary process, manifested himself in social Darwinism, and hesitated in many cases. The article also analyzes the problems of man and society in the Hadi’s philosophical outlook. It also reveals that Hadi’s worldview was paradoxical. Although he is more or less an idealist in terms of Islam and ontological as well as gnoseological issues, he has also made contradictory materialistic considerations.